Milk fermented with a 15-lipoxygenase-1-producing lactococcus lactis alleviates symptoms of colitis in a murine model - Saraiva, Tessália D. L. (2015)
Inflammatory bowel diseases (IBD), such as Crohn's disease and ulcerative colitis, is characterized by extensive inflammation due to dysregulation of the innate and adaptive immune system whose exact etiology is not yet completely understood. Currently there is no cure for IBD, thus the search for new molecules capable of controlling IBD and their delivery to the site of inflammation are the goal of many researchers. The aim of this work was to evaluate the anti-inflammatory effect of the administration of milks fermented by a Lactococcus (L.) lactis strain producing 15-lipoxygenase-1 (15-LOX-1) using a trinitrobenzenesulfonic acid-induced IBD mouse model. The results obtained demonstrated that 15-LOX-1 producing L. lactis was effective in the prevention of the intestinal damage associated to inflammatory bowel disease in a murine model. The work also confirmed previous studies showing that fermented milk is an effective form of administration of recombinant lactic acid bacteria expressing beneficial molecules.